Inclusive Entrepreneurship Education through Symbolic Capital and Entrepreneurial Marketing: Empowering Women in Sustainable SME Leadership - Putu Dyah Permatha Korry; Nyoman Sri Manik Parasari; Putu Irma Yunita; Caren Angelina Mimaki (Jurnal Ekonomi dan Bisnis Jagaditha, 2026)
Women entrepreneurs in developing economies, particularly in culturally complex regions like Bali, face structural challenges beyond finance and markets, including limited social legitimacy and leadership visibility. Despite their critical contributions to the MSME sector, especially in tourism and creative industries, they remain marginalized in decision-making and control over resources. This study investigates how symbolic and social capital interact with entrepreneurial marketing (EM) to foster sustainable marketing practices. Using a quantitative explanatory approach with SEM on 220 women entrepreneurs in Bali, the study examines the influence of symbolic and social capital on EM, and EM’s mediating role in achieving sustainability. Results show that symbolic capital, reflected in credibility and public recognition, has a stronger impact than social capital, and EM serves as a crucial mediator that transforms these resources into adaptive marketing strategies. The findings inform the design of inclusive, context-sensitive entrepreneurship education grounded in experiential and transformative learning.